1999
DOI: 10.1046/j.1365-2133.1999.02816.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the antibody response in oesophageal cicatricial pemphigoid

Abstract: Cicatricial pemphigoid (CP) is a subepidermal, autoimmune bullous dermatosis. It is classified as a clinical subset of bullous pemphigoid (BP). However, it differs from BP in some significant ways: (i) in CP mucosal involvement with clinical scarring is prominent; (ii) there is a prominent IgA class antibody response alone or in addition to the IgG class antibody response; and (iii) there is a heterogeneous antibody response in CP, whereas in BP the majority of the antibodies are directed against a 180-kDa hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The oesophageal biopsies of our patients did not clearly show any typical subepithelial split or positive DIF. Published data are consistent with a low rate of DIF positivity, except for one study, and the only published case report on isolated oesophageal EBA with positive IEM…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The oesophageal biopsies of our patients did not clearly show any typical subepithelial split or positive DIF. Published data are consistent with a low rate of DIF positivity, except for one study, and the only published case report on isolated oesophageal EBA with positive IEM…”
Section: Discussionsupporting
confidence: 74%
“…In the largest series with barium swallow for seven patients with classical MMP (previously called benign MM pemphigoid), no outcome information was given . Other series provided only immunological, or clinical, radiological and endoscopic findings, without any follow‐up information . Three studies comparable with ours reported clinical and radiological observations, with follow‐up in four, three and four patients, respectively …”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Some patients may have lesions of other stratified squamous epithelia such as of the larynx (Miziara et al , 2002; Whiteside et al , 2003), subglottis (Cole et al , 2000), oesophagus (Egan et al , 1999a; Sallout et al , 2000; Park et al , 2002), or nasal (Miziara et al , 2002), vulva (Ikegaya et al , 1999), penis (Fueston et al , 2002) or anus (Mutasim et al , 1993; Lilly et al , 1995), where scarring may cause serious complications. In rare cases, CP is disseminated (Provost et al , 1979; Kurzhals et al , 1995; Poon and McGrath, 1999).…”
Section: Less Common Lesionsmentioning
confidence: 99%